Post-Event Processing across Multiple Anxiety Presentations: Is it Specific to Social Anxiety Disorder?. Issue 5 (7th December 2015) - Perera, Stefan; Rowa, Karen; McCabe, Randi E.
Abstract : Background: Post-event processing (PEP) occurs when individuals engage in cognitive rumination following an event or interaction. Although the relation between PEP and social anxiety has been clearly demonstrated, it remains unclear whether PEP is limited to individuals with elevated social anxiety, or if it is also problematic among people with other anxiety presentations.Aims: The present study assessed PEP after the first session of group cognitive behavioural therapy (CBT) in individuals with a variety of anxiety presentations.Method: Participants with a principal diagnosis of SAD ( N = 25), those diagnosed with a principal other anxiety disorder with comorbid SAD ( N = 18), and those with principal other anxiety diagnoses with no SAD ( N = 43) completed baseline measures of social anxiety severity and state anxiety at their first session of CBT and measures of PEP one week later.Results: Participants with a principal diagnosis of SAD experienced the most PEP in the week following the first CBT session, while those with no comorbid SAD experienced the least. Those with comorbid SAD experienced intermediate levels of PEP. The strongest predictor of PEP was state anxiety during the first session.Conclusions: Results suggest that PEP is more problematic for clients with SAD as part of their clinical presentation. Clinical and theoretical implications are discussed.